Atypical Spitz Tumor Mimicking Pyogenic Granuloma: A Case Report and Literature Review - Yuka Nagasaka; Tomohiro Shiraishi; Takahiro Shibayama; Takashi Hibiya; Junji Shibahara; Akihiko Takushima (Journal of Plastic and Reconstructive Surgery, 2025)
Atypical Spitz tumors are one type of the Spitzoid melanocytic lesion, characterized by one or more atypical features, and often demonstrate indeterminate biological potential. Atypical Spitz tumors pose challenges in both clinical and pathological diagnoses. Herein, we report a case of a 1-year-old Japanese girl who presented with a rapidly enlarging lesion mimicking a pyogenic granuloma. The patient was ultimately diagnosed with an atypical Spitz tumor. The challenging clinical nature and diagnostic complexity of atypical Spitz tumors underscore their significance as crucial considerations in pediatric skin tumor differential diagnosis. Consistent consideration of atypical Spitz tumors within the diagnostic framework of pediatric cutaneous neoplasms is essential for timely and accurate assessment, thereby ensuring optimal patient care.